Faktor yang Mempengaruhi Kepala Sekolah dalam Mengambil Keputusan - Savitri, Sindi Dwi; Wahyuni, Sri (Lembaga Yasin AlSys, 2023)
This study aims to determine the factors that influence school principals in making decisions. This type of research is a literature study by utilizing various sources such as Google Scholar, Mendeley, and books. The findings of this study are that there are several factors that influence school principals in making decisions, namely organizational culture, self-concept, position/position, problems, situations, conditions, goals, internal organizational conditions, external organizational conditions, availability of necessary information, personality and decision-making skills.